Transforming Indonesia's Informal Sector: The Role of Industrialization in Manufacturing Industry - Krisnadi, Muhammad Faiz (Universitas Muhammadiyah Yogyakarta, 2023)
This study analyzes the need for Indonesia's massive industrialization in the manufacturing industry to address the persistent issue of informal employment. Indonesia's economy depends heavily on the informal sector, leading to a high unemployment rate and limited social protection. This study aims to explore the manufacturing industry's potential to create more formal employment opportunities and reduce informal employment. The objectives include analyzing the current state of the manufacturing industry, identifying the challenges and opportunities for growth, and proposing policy recommendations to promote industrialization. A qualitative research approach was used, with data collected through literature reviews, government reports, and library research. The study found that the manufacturing industry in Indonesia has excellent growth potential, given the country's large population, natural resources, and strategic location. However, several challenges include inadequate infrastructure, limited skilled labor, and bureaucratic hurdles. The proposed policy recommendations include improving infrastructure, providing vocational education and training, and streamlining regulations to attract foreign investment. The significance of this study lies in its focus on the potential of the manufacturing industry to create formal employment opportunities and reduce informal employment, which can contribute to poverty reduction and economic development in Indonesia. The study's novelty lies in its comprehensive analysis of the challenges and opportunities for industrialization in Indonesia and the proposed policy recommendations to address them.